Efficacy of Antimicrobial Dry Fog in Improving the Environmental Microbial Burden in an Inpatient Ward - Yashar Jalali; Andrea Kološová; Karol Džupa; Pavol Pavlovič; Monika Jalali; Peter Rácek; Nikola Zicháčková; Ján Kyselovič; Adriana Vasiková; Klaudia Glodová; Juraj Payer (Antibiotics)
Background/Objectives: In healthcare environments with high microbial loads, effective infection control measures are critical for reducing airborne and surface contamination. One of the novel modalities in the achievement of these goals is the use of antimicrobial mists, such as droplets, in the form of dry fog. Although the usage of dry fog in the disinfection of contained healthcare microenvironments is well known, the effect of such a system in terms of a meaningful reduction in the microbial burden in an open inpatient ward is unclear. Our objective was to assess the impact of scheduled dry fogging on microbial reduction in such settings. Methods: We collected air and surface samples from rooms receiving daily, biweekly, or no fogging (controls) over six months, establishing the baseline contamination and evaluating the reduction trends in treated rooms. The “reduction effect” was measured by tracking microbial isolation trends before and after treatment, while the “degree of reduction” assessed differences across rooms with varied disinfection schedules. Results: The results indicate that scheduled dry fogging significantly reduced microbial loads in treated rooms, especially with daily disinfection (SE = 64.484, p = 0.002). The airborne contamination in treated rooms showed a strong downward trend over time (SE = 19.192, p < 0.001). Surface contamination remained challenging due to frequent recontamination; however, treated rooms exhibited a consistent reduction in microbial presence (SE = 2.002, p = 0.010), confirming dry fogging’s role as a valuable adjunct to routine cleaning. Conclusions: In conclusion, this study highlights that dry fogging effectively reduces microbial loads in open, high-traffic healthcare environments, supporting its use as part of a multimodal infection control strategy.